Effect of feeding conventional or high-moisture, steam-flaked corn to finishing heifers - Sindt, J.J.; Kessen, T.J.; Sulpizio, M.J.; Loe, E.R.; Montgomery, Sean P.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Finishing heifers were fed diets containing either conventional (18% moisture) or high-moisture (36% moisture) steam-flaked corn. Increasing moisture concentration in flakes increased starch availability (P<0.01), but feeding heifers high-moisture flakes decreased (P<0.05) dry matter intake and average daily gain compared to heifers fed conventional flakes. Feeding heifers high-moisture flakes also numerically reduced hot carcass weight and ribeye area, but caused (P<0.01) heifers to deposit more fat over their 12th rib. Extreme levels of moisture in flaked corn improve starch availability but do not appear to increase heifer performance or carcass value. The interaction between moisture and flake density needs further evaluation.
Keywords: Beef; High-moisture, steam-flaked corn; Finishing heifers